MENTAL HEALTH COMMUNICATION PATTERNS BETWEEN CADRES OF PEKKA (WOMEN HEADED FAMILY EMPOWERMENT) AND CLIENTS (FEMALE HEADS OF HOUSEHOLDS) IN CIANJUR, WEST JAVA - Rodiah, Saleha; Dida, Susanne; Nurfalah, Farida; Nursari, Tita (Universitas Swadaya Gunung Jati, 2025)
The female head of the household has a double obligation as a mother who takes care of the children. They are also responsible for meeting the financial needs of family members. Single parent status not only makes them feel tired physically but also psychologically. The burden they feel is getting heavier when they face stereotypes from society that still considers widows as a negative status. This heavy burden of life makes them experience mental problems such as being moody, lamenting their fate, often crying and even being anti-social. They need communication partners to maintain peace of mind. PEKKA (Women Headed Family Empowerment) cadres are here to provide them with solutions. Cadres position themselves as friends to share problems with clients (female heads of households) until clients feel enthusiastic about living life again. This study used qualitative research with a case study approach to determine the pattern of mental health communication between cadres and clients to motivate clients to ascend from adversity. The results show that they communicate by opening chit-chat, persuasive talking, casual chat, paraphrasing, summarizing, and closing chit-chat. In these activities they also showed nonverbal communication, use electronic communication media, and leave messages to cadre friends or clients.